A study on reported fire incidents in major hospitals of India - Patharla, Shyam Siddharth Rao; Pyreddy, Souri Reddy; Panthagani, Shilpa N. (International Journal Of Community Medicine And Public Health, 2020)
Background: An uncontrolled fire is dangerous especially in the healthcare establishments as they frequently cater to the sick who often require assistance. We studied the various aspects of fire incidents that occurred in major Indian hospitals through media reports in the past decade (January 2010 to December 2019). It is our intention that this study would act as a reference to prioritize and stimulate research in hospital fire safety. Methods: An extensive internet search was done for news reports/articles on fire incidents in major hospitals by mainstream media outlets. Major hospitals were those with more than 100 in-patient beds. Results: 33 major fire incidents were reported during the defined period. The most common cause of fire was due to electrical short circuit 78% with air conditioners being the most common source. Functional firefighting systems were reported in 19 incidents. Fires originated at or near intensive care units (ICU’s) in 10 instances. 72.72% accidents occurred at night (8:01 p.m. to 7:59 a.m.). Casualties were reported in 39% of the fire accidents. Conclusions: The most common cause of fire accidents is electrical short circuit. Hospitals need to prioritize periodic testing of firefighting systems and regular training of staff on their use. Judicious placement of electrical equipment combined with oxygen monitoring devices in intensive care areas is recommended. Storage of flammable materials and placement of central gas supply points should be away from the vicinity of patient care areas and always in conjunction with robust fire detection and control methods. Hospitals should adhere to their planned capacity.